Thermal analysis of solidification process and mechanical properties in heavy section ductile iron casting - Chen, Wei Ping (2013)
A heavy section ductile casting (HSDIC) with dimensions of Φ590 mm×800 mm was prepared. Cooling curves at the center, at 85 mm from the center, at 170 mm from the center and at 255 mm from the center of the casting were recorded and analyzed. The results show that the precipitation of initial graphite, nucleation of eutectic cell and mass eutectic reaction at 255 mm from the center were all earlier than the other three locations. Moreover, it takes the longest time of 53 minutes of recalescence at 170 mm from the center with the highest temperature rise of 7 °C, though the cooling rate at this location is not the lowest in the casting, the mechanical properties are the worst. In addition, the largest amount of chunky graphite appears at 170 mm from the center.